2009
DOI: 10.1111/j.1743-6109.2008.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Combined Oral Therapy with Tadalafil and Alfuzosin: An Integrated Approach to the Management of Patients with Lower Urinary Tract Symptoms and Erectile Dysfunction. Preliminary Report

Abstract: Introduction Alpha1-blockers (AB) are the first-line monotherapy for lower urinary tract symptoms (LUTS). Phosphodiesterase type 5 (PDE5) inhibitors are the first-line treatment for erectile dysfunction (ED). Numerous studies have supposed a significant association between ED and LUTS, but a causal relationship cannot be established. Aim The aim was to evaluate the efficacy of a combined therapy with an AB (alfuzosin) and PDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 46 publications
6
89
1
Order By: Relevance
“…29 Supporting this is that the baseline Qmax of 14.54 ± 3.26 ml s À1 in the present study is high compared with those recorded in previous studies. [23][24][25][26] In comparison with Kaplan et al and Tuncel et al, the full dose of mirodenafil, which we used might result in similar outcomes of improvement for LUTS despite only two times per week. In addition, we investigated two groups to examine correlation on improvement of IIEF-5 and IPSS.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…29 Supporting this is that the baseline Qmax of 14.54 ± 3.26 ml s À1 in the present study is high compared with those recorded in previous studies. [23][24][25][26] In comparison with Kaplan et al and Tuncel et al, the full dose of mirodenafil, which we used might result in similar outcomes of improvement for LUTS despite only two times per week. In addition, we investigated two groups to examine correlation on improvement of IIEF-5 and IPSS.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, only the combination therapy was associated with a significant improvement in the IIEF (Po0.001). Moreover, when Liguori et al 25 conducted a study with 66 BPH patients who had had LUTS for at least 6 months to determine the efficacy of alfuzosin 10 mg OAD and/or tadalafil 20 mg every other day, they found that while the IPSS was significantly improved in the alfuzosin monotherapy group (27.2%), it was even better in the combination therapy group Combination therapy with mirodenafil and a 1 -blocker JY Lee et al (41.6%). Qmax was also improved in all three groups (21.7%, P ¼ 0.006 for alfuzosin; 9.5%, P ¼ 0.044 for tadalafil; 29.6%, Po0.001 for combination), with the combination group showing the best improvement.…”
Section: Discussionmentioning
confidence: 98%
“…94 Two more studies investigating the combination of a-blocker and PDE-5 inhibitor to treat LUTS and ED concluded that the combination of the two drugs is safe and more effective than monotherapy with either agent to improve both voiding and sexual dysfunction in men with LUTS suggestive of BPH. 95,96 Effects of testosterone used for treatment of hypogonadism on LUTS A number of studies involving the use of testo sterone for ED or late onset hypogonadism, investigated the effects of testosterone administration to elderly men on symptoms of LUTS. Saad et al 97 described the effects of administration of parenteral testosterone undecanaote over 12 months.…”
Section: Luts and Ed: Effects On Clinical Managementmentioning
confidence: 99%
“…Also, relative international prostate symptom scores (IPSS) were the lowest in the combination arm (a 24% decrease from baseline), which supports other clinical studies showing sildenafil's independent positive effect on IPSS reduction in men with benign prostatic hyperplasia. 32,33 Liguori et al 34 examined tadalafil and alfuzosin in 66 men with LUTS and ED. As seen in earlier studies, combination therapy again showed benefits in comparison to monotherapy in treating both of these disease processes.…”
Section: Pde5i Plus A-adrenergic Receptor Antagonistmentioning
confidence: 99%